PERTANGGUNGJAWABAN DAN UPAYA HUKUM TERHADAP PERBUATAN PERUNDUNGAN YANG DILAKUKAN PADA LINGKUNGAN SEKOLAH BERDASARKAN KETENTUAN UNDANG-UNDANG NOMOR 35 TAHUN 2014 TENTANG PERLINDUNGAN ANAK - Moh Iqbal Firmansyah Palawa (LEX PRIVATUM, 2024)
The purpose of writing this study is to find out how the school is held accountable for perpetrators of bullying carried out in the school environment according to statutory regulations and to find out what legal measures are taken against perpetrators of bullying according to positive law in Indonesia. The research method used in this study is normative juridical research method with a statutory approach and a conceptual approach. The conclusion obtained is that if bullying occurs at school, the principal and teachers at the school must be responsible for the bullying that occurs in the school environment, namely by providing help and quick healing to the victims of bullying. Regarding children as perpetrators of bullying, sanctions must be given to them by looking at the losses or things experienced by the victim and if the losses experienced by the victim are not too serious then the case can be resolved by means of diversion. Keywords: Bullying, Child Protection